2015
DOI: 10.1016/j.msea.2015.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Alternative phase transformation path in cryogenically treated AISI D2 tool steel

Abstract: This study based on dilatometry test and microstructural observations showed a different phase transformation path during conventional heat treatment of AISI D2 tool steel instead of the traditionally expected fully martensitic transformation. Transformation started with carbide precipitation and continued with allotriomorphic ferrite, Widmanstätten ferrite, acicular ferrite, and finally bainite formation. This microstructure showed microhardness value of 730 HV, which is very high for conventionally cooled sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
3
7
0
Order By: Relevance
“…Apparently, the XRD analysis results confirmed that sub-zero treatment can indeed remove retained austenite. In other words, the retained austenite had been almost transformed into martensite after subzero treatment, which also agrees with the above literatures and our previous studies [2,15,16]. 2 T + HT, and 0.2 T + SZ specimens.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Apparently, the XRD analysis results confirmed that sub-zero treatment can indeed remove retained austenite. In other words, the retained austenite had been almost transformed into martensite after subzero treatment, which also agrees with the above literatures and our previous studies [2,15,16]. 2 T + HT, and 0.2 T + SZ specimens.…”
Section: Resultssupporting
confidence: 93%
“…It can be improved the mechanical properties by using a series of heat treatments. Cryogenic treatment (also known as sub-zero), as an effective way to improve the properties of tool steels, since it enhances the transformation of retained austenite to martensite [15][16][17][18]. Therefore, we added Cr 3 C 2 -TaC-TiC carbides to Vanadis 23 powders as an innovative composite material, aimed to explore a series of vacuum sintering processes, sub-zero and heat treatments for Vanadis 23 composites, and further examined the effects on the sintering behaviour, strengthening mechanism, and mechanical properties of Cr 3 C 2 -TaC-TiC strengthened Vanadis 23 composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…This phase transformation causes a remarkable length decrease and can be clearly detected during the dilatometry test [4,9,12,18].…”
Section: Introductionmentioning
confidence: 87%
“…Cryogenic treatment (also known as sub-zero) is an effective way to improve the properties of tool steels, since it enhances the transformation of austenite to martensite. In recent years, several papers have been published that sub-zero treatment can improve wear resistance of tool steels [16,17]. Normally, the temperature range of sub-zero normally is from −125 to −196°C .…”
Section: Methodsmentioning
confidence: 99%